ENFORCEMENT OF THE CREDIT AGREEMENT WITH THE GUARANTEE OF THE MORTAGE FOR THE DEVELOPER OF RESIDENTIAL CONSTRUCTION WITH CREDIT - I Nyoman Widana (Faculty of Law, Universitas Sebelas Maret, 2017)
In article 2 paragraph (2) of the Mortgages Law on section 22 subsection (9) has deleted the mortgages rights on the object that is concerned to be logged by the land Office over the books of the land and rights of a dependent as well as the Certificate of land entitlement which has been free from the rights of the original relations. However, section 22 subsection (9) of the mortgages law does not specify the logging enforcement of time limit by the Office of the Land Commission as specified in article 22 paragraph (8). This research aims to analyse the enforcement of credit agreement residential construction with dependent rights in the city of Mataram. What are the factors affecting the enforcement of the rights of dependent credit residential construction in the city of Mataram and how is the responsibility of the notary against the deed of credit agreement made in residential construction. This research is empirical legal research seeking at how the law in reality field. The research uses descriptive qualitative analysis supported by qualitative approaches. Based on the results of the research, enforcement of a residential construction that charged on right dependents between company and bank has previously started by an agreement in which the agreement was made to facilitate the parties in conducting the process of loading a dependent right which the rights and obligations of the parties are set forth in the cooperation agreement.